Enhancing Communication Skills in Maritime English: Effective Teaching Strategies and Key Influencing Factors - Katuuk, Nadia Novernia Cristy (Indonesian Journal Publisher, 2025)
This research explores the enhancement of communication skills through effective teaching strategies in Maritime English. Given the critical role of English in maritime operations, particularly for sailors, ship agents, and port authorities, the study emphasizes the need for effective language training to ensure safety and operational efficiency. Through a review of recent literature, the research identifies key teaching strategies, including task-based learning, simulation-based training, and cultural integration, that significantly improve students' proficiency in Maritime English. This reaseacrh also highlights factors such as the use of technology, the expertise of educators, and resource availability as critical elements for the successful implementation of these strategies. Despite the existing methods, research on teaching strategies specific to Maritime English remains limited, necessitating further exploration in this field. The findings underscore the importance of developing innovative and contextually relevant teaching methods to equip future maritime professionals with the necessary communication skills for real-world scenarios.